A STUDY OF CHALLENGES FACED BY PARENTS OF CHILD DIAGNOSED WITH AUTISM SPECTRUM DISORDER (ASD) - Dr. Vidhu Rajput (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Autism spectrum disorders (ASD) are a diverse group of conditions. They are characterized by some degree of difficulty with social interaction and communication. Other characteristics are atypical patterns of activities and behaviours, such as difficulty with transition from one activity to another, a focus on details and unusual reactions to sensations. The abilities and needs of autistic people vary and can evolve over time. While some people with autism can live independently, others have severe disabilities and require life-long care and support. Autism often has an impact on education and employment opportunities. In addition, the demands on families providing care and support can be significant. Societal attitudes and the level of support provided by local and national authorities are important factors determining the quality of life of people with autism